Solid Wastes Wastewater and Remediation Costs in An Urban Slum: The Case Study of A Gypsy Camp in Napoli (S Italy) - Casazza, Marco; Accardo, Pier Luigi; Severino, Vincenzo; Lega, Massimiliano (Journal of Environmental Accounting and Management, 2026)
Slums represent a sort of black box within the urban environment, generating multiple impacts, that are often acknowledged, but forgotten by urban planners and policy-makers when envisioning the future of cities, due to the dimension of social exclusion in which slum dwellers live. These criticalities pose a further threat to urban sustainability. The first problem is revealed by the lack of quantifications about many environmental and socio-economic factors, as well as by a general lack of understanding about slums as systems. This study is aimed at overcoming the present knowledge weakness, developing a preliminary site-specific system representation of a slum as a system. In particular, a case study of a Gypsy camp in Napoli (S Italy) was chosen for such a purpose. Focusing on solid waste, an approximate evaluation of informal waste picking activity was performed. Basic parameters of generated wastewater, which is dispersed in the environment due to the absence of any sewerage infrastructure, are accounted according to environmental engineering standards. In addition, considering a second abandoned camp (Brecce Sant’Erasmo, Napoli, Italy), specific-site remediation costs were calculated. Results evidence the necessity of a better understanding of resources flows within slums. A first planning action for the studied area would be to separate the areas for waste processing with respect to living areas. Basic infrastructures for solid waste and wastewater management are also necessary to improve the life quality of slum dwellers, while reducing the existing impacts. Finally, also a study to detail atmospheric emissions characteristics would be desirable. Specific upgrading solutions are indicated on the basis of the existing literature. They include planning and monitoring actions, together with the development of engineered solutions for waste and wastewater management.